Protocolo de práctica clínica para la adaptación de lentes de contacto en superficie ocular sana - Vega Casallas, Angélica (Universidad Antonio Nariño, 2021)
Care Protocol is defined as the logical and detailed sequence of a series of procedures and activities to be carried out in health care in a given environment, without allowing the personnel involved in the care to change the course of the actions carried out. It includes the protocols that the health service provider defines and those established in the regulations that regulate the matter as mandatory